Réponses

2013-06-11T19:04:16+02:00

Bonsoir

 

A = x²+2x +x +2 +x² +3x +2x +6

A = 2x² +8x +8

 

A = (x+2)(x+1)+(x+3)

A = (x+2)(x+1+x+3)

A = (x+2)(2x+4)

 

B = (2x+1) + (2x² -10x +x -5) + (2x² +6x+x+3)

B = 2x+1 +2x² -9x -5 +2x² +7x+3

B = 4x² -1

 

B = (2x+1) (x-5) +(x+3)

B = (2x+1)( x-5+x+3)

B = (2x+1)(2x -2)

Meilleure réponse !
2013-06-11T19:20:34+02:00

Développement :

A = (x+1) (x+2) + (x+2) (x+3)

A =  x² +2x +x +2 +x² +3x +2x +6

A = 2x² +8x +8

 

Factorisation 

A = (x+1) (x+2) + (x+2) (x+3)                Facteur commun = (x+2)

A = (x+2) (x+1+ x+3)

A = (x+2) (2x +4)

 

Développement B

B= (2x+1) +( 2x+1)(x-5) + (2x +1) (x+3)

B = (2x+1) + (2x² -10x +x -5) + (2x² +6x+x+3)

B = 2x+1 +2x² -9x -5 +2x² +7x+3

B = 4x² -1

 

Factorisation B

B= (2x+1) +( 2x+1)(x -5) + (2x +1) (x+3)              Facteur commun (2x+1)

B = (2x+1)  (x -5) +(x+3)

B = (2x+1)( x-5+x+3)

B = (2x+1)(2x -2)